Haboo : Native American Stories from Puget Sound - LaPointe, Jill; Hilbert, Vi; Hilbert, Vi; Hilbert, Ron; Hess, Thom, 1936-2009 (Book collections on Project MUSE., 2020)
"The stories and legends of the Lushootseed-speaking people of Puget Sound were an important part of the oral tradition by which beliefs, values, and customs were handed from one generation to another. Vi Hilbert, a Skagit Indian, grew up at a time when many of the old social patterns survived and when everyone still spoke the ancestral language. As an adult, when she realized that native language and culture were being forgotten, she began to work with linguists and anthropologists in recording and translating as much of the Lushootseed oral tradition as possible. Haboo is her collection ofthirty-three stories"--